Statistics - Freedman, David; Pisani, Robert; Purves, Roger (New Delhi Viva Books, 2009)
Statistics is a comprehensive guide to help students understand the importance of statistics across various fields like political science, medicine, psychology and genetics, among others. The book comprises chapters on controlled experiments, observational studies, the Histogram, the average and standard deviation, measurement error, regression, the accuracy of percentages, and the Chi-square test. In addition, the book consists of several several examples, illustration and tables to help students understand the concepts of statistics better.
Keywords: Correlation; Regression; Measurement error; Average and standard deviation